Analisis Perbandingan Pengalaman Pengguna Pada Aplikasi Music Streaming Menggunakan Metode UX Curve (Studi Pada Spotify dan JOOX) - Zakia Rahmasanti Karyono; Yusi Tyroni Mursityo; Hanifah Muslimah Az-Zahra (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2019)
The rapid development of technology changes our lifestyles, one of them is switching to listening to music through music streaming application instead of digital music application. This music streaming application enables the user to listen to the different types of music legally by streaming. Millenials are the perfect target audience for music streaming application. The increase in this trend of listening to music online brings up a hypothesis if the application has a good user experience, thus it creates a better response. One of the aspects that influences the development of the application is the perception of the user or far more familiar named as user experience. That is the reason why this research is conducted upon the comparison of user experience between Spotify and JOOX as the most subscribed music streaming applications in Indonesia. As the kind of application that is used daily, so A long-term research method like UX Curve is needed. UX Curve can capture every change in user experience from the beginning of the usage until recent usage by relying on the user's memory. There were 20 respondents, ages ranging from 16 to 30 years old, that were needed to conduct this research towards five aspects of UX Curve: general UX, attractiveness, ease-of-use, utility, and degree-of-usage. The result was a that shows Spotify has a better user experience so they assume Spotify is a good application for them thus resulting in the tendency to keep using it as their trusted music streaming application.